Sosialisasi Materi Literasi Keuangan dalam Mengelola Keuangan Pribadi Pada Siswa/i Kelas XI SMAN 46 Jakarta - Ossi Ferli; Deni Wardani; Nadya Kamila; Karina Putri Destania; Riedmen Gifar Widagdo; Lavenia Permata Sari (I-Com: Indonesian Community Journal, 2024)
The service activity at SMAN 46 Jakarta aims to improve students' financial literacy through materialpresentation and pre-test and post-test surveys. Descriptive statistical method was used to analyze thepre-test and post-test survey data. This analysis includes calculating the average score obtained bystudents before and after the activity. Financial literacy is the understanding, behaviour, and attitudeneeded to manage and utilize financial resources ef ectively to achieve optimal results. In Indonesia,the level of financial literacy is still low, to improve the financial literacy of the younger generation. Ofthe 34 grade 11 students who participated, their understanding of financial literacy improvedsignificantly after the socialization. Before the activity, students' understanding of financial literacywas low. After the socialization, there was a significant increase in students' understanding andinterest